Pelatihan Nilai Tambah Produk Agroindustri Lokal dan Literasi Keuangan Berbasis Digital Pada Ibu-Ibu PKK Desa Manimbahoi Kecamatan Parigi Kabupaten Gowa - Rasyid, Nadir; Mira; kmal Saleh, Muh. I; Aprilianti M, Firda; Aisyah Haris Dalle, Sitti (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
The development of local agro-industrial products in Manimbahoi Village, Parigi Subdistrict, Gowa Regency, aims to improve the welfare of the community through the empowerment of the PKK group. Most of the village residents depend on agriculture, with commodities such as tomatoes and vegetables often experiencing price declines and losses due to limited marketing and poor financial management. The objective of this activity is to provide training on product diversification, digital marketing, and digital-based financial literacy. The method applied uses a “Learning by Doing” approach, which consists of five stages, namely problem identification, planning, implementation, evaluation, and continuous mentoring. Training activities include the manufacture of agriculture-based processed products, product packaging, marketing through social media, and digital financial management. A total of 30 women from the Manimbahoi Village PKK participated in the training. The main results achieved include improved skills in processing tomatoes into value-added products such as tomato sauce and sambal, as well as torakur (date-flavored tomatoes), and a better understanding of financial management and digital marketing. Participants were also trained in creating attractive packaging and e-catalogs to promote products online. Further assistance has improved marketing efficiency and business management, opening up broader economic opportunities for the local community. This training has successfully improved the skills and capacity of PKK women in managing local agro-industrial businesses, as well as introducing them to digital financial literacy that supports business sustainability. This success demonstrates the importance of community involvement in empowerment-based programs to improve the economic welfare of villages.